Africa RISING-Cowpea Baby Trial in Northern Ghana - International Institute of Tropical Agriculture; Ministry of Food and Agriculture, Government of Ghana; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2016)
Project title: Cowpea Baby Trial in Northern Ghana Project abstract: This project aims to evaluate the performance of cowpea varieties by farmers. Project website: http://africa-rising.net